PENGUJIAN MEDIA TANAM KOMPOS SAMPAH DOMESTIK DAN RESIDU LUBANG SAMPAH TERHADAP KANDUNGAN HARA N, P, K SERTA PRODUKSI SAWI (Brassica oleraceae L.) PADA TANAH INCEPTISOL - Muhammad Maksum Harahap; Abdul Rauf; Muhammad Madjid B. Damanik (Jurnal Agroekoteknologi, 2013)
This research aimed to evaluate the effect of the domestic waste of compost growing media and theresidual of waste pit and the combination of both on the contents of N, P, K also the production ofmustard (Brassica oleraceae L.) on inceptisol soil. This research was conducted in the compostyard in Kecamatan Sunggal Kabupaten Deli Serdang and analysis continued in the riset andtechnology laboratory of agricultural faculty of university of North Sumatera. This study usedRandomized Blok Design (RBD) which is consisted of 9 treatments and 3 replications. Thetreatments are M1 (100% soil), M2 (75% soil + 25% compost), M3 (50% soil + 50% compost), M4(25% soil + 75% compost), M5 (75% soil + 25% residues of the waste pit), M6 (50% soil + 50%residues of the waste pit), M7 (25% soil + 75% residues of the waste pit), M8 (50% compost+ 50%residues of the waste pit), M9 (100% residues of the waste pit). Where the result is that theprovision of domestic waste compost and residues of the waste pit and the combination of both,very significantly increased value the pH of the soil, C-organic, N-total, P-available, K-exchange aswell as the production of the wet weight mustard plant on inceptisol soil.